1999
DOI: 10.1021/jp9833146
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on the N(2D, 2P) + CH4 and CD4 Reactions:  The Role of Nonadiabatic Transitions on Thermal Rate Constants

Abstract: Thermal rate constants for the N(2D,2P) + CH4 (CD4) reactions have been measured using a technique of pulse radiolysis−resonance absorption in the temperature range between 223 and 298 K. Activation energies determined from the temperature dependence were about 1.5 and 1.0 kcal/mol for the reactions of N(2D) and N(2P), respectively. The H/D kinetic isotope effects were about 1.8 and 1.6 for N(2D) and N(2P), respectively. The rate constants for N(2P) + CH4 were much smaller than those for N(2D) by a factor of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 23 publications
4
45
1
Order By: Relevance
“…An indirect identification of CH 2 NH in the atmosphere of Titan has indeed been reported by Vuitton et al (2006Vuitton et al ( , 2007 and Yelle et al (2010 Table 3). As for N( 2 D) reaction, Takayanagi et al (1999) measured a rate constant for the reaction with CD 4 , which was found to be slightly lower than for CH 4 . Both Umemoto et al (1985) and Takayanagi et al (1999) (±25%) for C 2 H 2 k = 6.25 × 10 −11 cm 3 s −1 (±25%) for C 2 D 2 .…”
Section: Reaction N ( 2 D) + Chmentioning
confidence: 99%
See 4 more Smart Citations
“…An indirect identification of CH 2 NH in the atmosphere of Titan has indeed been reported by Vuitton et al (2006Vuitton et al ( , 2007 and Yelle et al (2010 Table 3). As for N( 2 D) reaction, Takayanagi et al (1999) measured a rate constant for the reaction with CD 4 , which was found to be slightly lower than for CH 4 . Both Umemoto et al (1985) and Takayanagi et al (1999) (±25%) for C 2 H 2 k = 6.25 × 10 −11 cm 3 s −1 (±25%) for C 2 D 2 .…”
Section: Reaction N ( 2 D) + Chmentioning
confidence: 99%
“…As for N( 2 D) reaction, Takayanagi et al (1999) measured a rate constant for the reaction with CD 4 , which was found to be slightly lower than for CH 4 . Both Umemoto et al (1985) and Takayanagi et al (1999) (±25%) for C 2 H 2 k = 6.25 × 10 −11 cm 3 s −1 (±25%) for C 2 D 2 . The rate constant has been measured by two groups (Fell et al 1981;Takayanagi et al 1998b; see Table 3) measured the rate constants over the temperature range 223-293 K and reported values of k = 1.6 × 10 −10 exp (−270/T) cm 3 s −1 and 1.4 × 10 −10 exp(−240/T) for C 2 H 2 and C 2 D 2 , respectively.…”
Section: Reaction N ( 2 D) + Chmentioning
confidence: 99%
See 3 more Smart Citations